Effect of physical activity on body weight of elementary school children - Patrycja Aleksy; Martina Grot; Maciej Nigowski; Ewelina Sobecko; Mateusz Grajek; Karolina Krupa-Kotara (Nicolaus Copernicus University in Toruń, 2023)
BACKGROUND: Physical activity is an extremely important part of diet and carries a number of health-promoting benefits towards health. A distinction is made between exercise-related physical activity and spontaneous physical activity. The diet of school-aged children is of particular importance, due to the development of the body. The consequence of low physical activity with an inadequate diet generates the development of various diseases. Purpose: The purpose of this study is to evaluate the impact of physical activity on the body weight of students of elementary schools 1 and 2 in Radzionków. Material and methods: The study included 260 students of grades I-VIII of Elementary Schools Nos. 1 and 2 in Radzionków. A proprietary questionnaire addressed to the parents of the students containing questions about the students' anthropometric measurements, physical activity and eating habits was used to conduct the study. Results: Physical activity is at a high level. Most children had a normal body weight. Among the students surveyed, 71% indicated that they mainly spend their free time in active form. Students participate in swimming classes in the greatest number. Several times a week (55%) children attend extra-curricular activities. Consumption of sweets and fast food is at a low level. Eating the recommended daily serving of fruits and vegetables affects only 43% of children. Among the most commonly consumed beverages, 84% of children choose water at 1-1.5 liters per day. Conclusions: A significant part of the study group has a normal body weight, so it can be assumed that physical activity combined with appropriate eating habits has a health-promoting effect on body weight.